Implementation and Reconfiguration of Robot Operating System on Human Follower Transporter Robot - Saphala, Addythia; Tanaya, Prianggada Indra (Bina Nusantara University, 2015)
Robotic Operation System (ROS) is an im- portant platform to develop robot applications. One area of applications is for development of a Human Follower Transporter Robot (HFTR), which can be considered as a custom mobile robot utilizing differential driver steering method and equipped with Kinect sensor. This study discusses the development of the robot navigation system by implementing Simultaneous Localization and Mapping (SLAM).